Relationship between disease perception and feelings of powerlessness in lymphoma patients: the mediating effect of social support and level of hope - Zhu, Yingying; Hua, Haiying; Sheng, Li; Zhou, Jingfen; Ye, Long; Gu, Siyu (Frontiers in Psychiatry, 2025)
ObjectivesLymphoma patients often experience significant physical and psychological stress, with feelings of powerlessness negatively impacting their health. While social support and hope are crucial for improving mood and coping with disease, their mechanisms in relation to disease perception and powerlessness remain unclear. This study aimed to examine the relationship between disease perception and feelings of powerlessness in lymphoma patients, focusing on the mediating roles of social support and hope.MethodsFor a cross-sectional design, 311 lymphoma patients were surveyed using the Brief illness perception questionnaire, Powerlessness assessment tool, Social Support Rating Scale, and Herth’s Hope Scale, and were statistically analyzed using the software SPSS 27.0 and PROCESS version 4.1.ResultsA correlation was found between the disease perception, social support, hope level, and feeling of powerlessness of lymphoma patients (P < 0.01). There was a positive correlation between perceptions of illness and powerlessness (β= 0.291, P<0.001), and disease perception could influence powerlessness through three indirect pathways: the separate mediating effect of social support [β= 0.057, 95%CI (0.029 0.091)], the separate mediating effect of level of hope [β= 0.07, 95%CI (0.034 0.107)], and the chain mediating effect of social support and hope level [β= 0.019, 95%CI (0.008 0.033)]. Social support and level of hope played a partial medium mediating effect in the effect of perceived disease on feelings of powerlessness, accounting for 13.04% and 16.02% of the total effect, respectively, and the chained mediating effect of both accounted for 4.35% of the total effect.ConclusionsDisease perception and powerlessness were positively correlated in lymphoma patients, and in addition, social support and level of hope mediated the relationship. This conclusion provides a theoretical basis and guidance for nursing interventions to reduce powerlessness in lymphoma patients.